2010
DOI: 10.1158/1535-7163.mct-09-0559
|View full text |Cite
|
Sign up to set email alerts
|

BAMLET Activates a Lysosomal Cell Death Program in Cancer Cells

Abstract: A complex of human α-lactalbumin and oleic acid (HAMLET) was originally isolated from human milk as a potent anticancer agent. It kills a wide range of transformed cells of various origins while leaving nontransformed healthy cells largely unaffected both in vitro and in vivo. Importantly, purified α-lactalbumins from other mammals form complexes with oleic acid that show biological activities similar to that of HAMLET. The mechanism by which these protein-lipid complexes kill tumor cells is, however, largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
98
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 38 publications
10
98
0
2
Order By: Relevance
“…HAMLET has also been shown to affect mitochondria [31] and induce apoptosis-like cell death with caspase activation, PS externalization and chromatin condensation irrespective of the p53 and bcl-2 status of the cells [32] and to cause changes in proteasome structure and function [33]. In addition, it has been shown by Aits et al that HAMLET induces autophagy [34], while Rammer et al see activation of the lysosomal death pathway in response to BAMLET treatment, but that the cytotoxicity of BAMLET does not depend on autophagy [18]. However, apart from these quite specific effects of HAMLET, there is also evidence of a more crude effect connected to membrane interactions and alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAMLET has also been shown to affect mitochondria [31] and induce apoptosis-like cell death with caspase activation, PS externalization and chromatin condensation irrespective of the p53 and bcl-2 status of the cells [32] and to cause changes in proteasome structure and function [33]. In addition, it has been shown by Aits et al that HAMLET induces autophagy [34], while Rammer et al see activation of the lysosomal death pathway in response to BAMLET treatment, but that the cytotoxicity of BAMLET does not depend on autophagy [18]. However, apart from these quite specific effects of HAMLET, there is also evidence of a more crude effect connected to membrane interactions and alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, complexes of peptide fragments of α-LA have been formed by mixing the protein with OA in ethanol dispersed in a buffer [15] and BAMLET has also been made by mixing α-LA with the more soluble sodium salt of OA, sodium oleate [16]. The -LA:OA complexes are cytotoxic to a wide range of cancer cells [17][18][19] as well as some types of primary cells [17]. The structure of the H/BAMLET has been a subject of multiple studies, often with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…These include OA-conditioned anion exchange chromatography using either a DEAE-Trisacryl M in the conventional method [3,5,6,19] or a DEAE-Sepharose column in an alternative method [53]. Direct mixing under heat denaturation [30,36,52], heat denaturation of -LA and OA-conditioned anion exchange chromatography [62], direct mixing in solution at room temperature with alternated pH conditions [45,48,49,63], direct mixing followed by anion exchange chromatography [61] and alkaline conditions [64] have also been used.…”
Section: Methods Of Hamlet or Hamlet-analog Preparation In Vitromentioning
confidence: 99%
“…Initial gas chromatography and mass spectrometry data suggested that the average number of oleic acid molecules bound in the HAMLET complex was 0.9, with some batch variation [6]. The assumption of a 1:1 protein/fatty acid ratio was also reported in the preparation of BAMLET by chromatography [61]. By gas chromatography and mass spectrometry a later study estimated an -LA to OA ratio of 1:5.4 in a HAMLET complex prepared by the OA-preconditioned anion exchange chromatography method [38].…”
Section: Stoichiometry Of the Protein And Fatty Acid In Hamlet And Hamentioning
confidence: 98%
“…In an acidic environment, α-lactalbumin forms the HAMLET (human α-lactalbumin made lethal to tumor cells) complex with oleic acid which inhibits the proliferation of various tumors by an apoptosislike mechanism [Svanborg et al 2003]. The BAM-LET complex, the bovine equivalent of HAMLET, has been recently found to exert a strong cytotoxic effect on eight lines of tumor cells by increasing the permeability of the lysosomal membrane [Rammer et al 2010].…”
Section: Nomenclature and Molecular Properties Of Milk Proteinsmentioning
confidence: 99%